Bioimpedance-assessed volume overload predicts interdialytic hypertension and disrupted circadian blood pressure rhythm in maintenance hemodialysis patients - Qian Wang; Min Li; Shipeng Shen; Yao Hu; Yongzhe Chen; Changchang Liang; Ke Yu; Ying Li; Yanqing Chi; Lu Bai (PLoS ONE, 2026)
Objective Hypertension and abnormal circadian blood pressure (BP) rhythm are prevalent in maintenance hemodialysis (MHD) patients, and are closely associated with cardiovascular diseases (CVD) and increased all-cause mortality. Volume overload represents a critical factor in effectively controlling hypertension. Bioelectrical Impedance Analysis (BIA) has been validated as an accurate method for assessing volume status. This study aimed to investigate the predictive value of BIA-derived volume indicators for hypertension and circadian BP rhythm abnormalities in MHD patients, providing a theoretical basis for optimizing volume control and BP management. Methods We used body composition monitor to assess pre-dialysis volume status and employed 44-hour interdialytic ambulatory BP monitoring (ABPM) to obtain BP parameters. Comparative analyses were conducted between controlled vs. uncontrolled ABPM groups, and normal vs. abnormal circadian BP rhythm groups. Univariate and multivariate analyses were performed to identify correlations and independent predictors, with receiver operating characteristic (ROC) curves determining optimal predictive cut-off values. Results Patients in the uncontrolled ABPM group exhibited higher levels of intact parathyroid hormone (iPTH), post-dialysis serum creatinine (Post-HD Scr), post-dialysis urea nitrogen (Post-HD BUN), overhydration (OH), extracellular water (ECW), body surface area-adjusted ECW (ECW/BSA), ECW to total body water ratio (ECW/TBW) and ECW to intracellular water ratio (ECW/ICW), but lower Kt/V and URR. The abnormal circadian BP rhythm group showed higher iPTH, OH, ECW, ECW/BSA and ECW/ICW. Significant correlations were observed: 44h SBP correlated positively with iPTH, OH, ECW/TBW, ECW/ICW, and negatively with Kt/V, URR; 44h DBP correlated positively with iPTH and OH; nocturnal systolic BP decline rate (NSDP) showed negative correlations with iPTH, OH. Multivariate logistic analysis identified OH > 2.35L, ECW/ICW > 0.945 and iPTH > 240.6 pg/ml as independent predictors for hypertension, while OH > 1.55L and iPTH > 203.75 pg/mL predicted abnormal circadian BP rhythm (all p < 0.05). Conclusion BIA-derived indicators of volume overload, particularly OH and ECW/ICW, can guide ABPM management in MHD patients and improve long-term outcomes.